2018
DOI: 10.1097/shk.0000000000000936
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Mortality Score Using Delta Neutrophil Index and the Thrombotic Microangiopathy Score for Prognostication in Critically Ill Patients

Abstract: The SMS is a more rapid, simple prognostic score for predicting 28-day mortality and stratifying risk than the APACHE II or SOFA scores. However, external validation using a larger sample is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…Characteristics of the mortality prediction models and underlying derivation cohorts are presented in Table 1. In all, 19 mortality prediction models (44%) were developed using prospectively collected data specifically gathered for the development of the prediction model, 6,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] whereas 24 (56%) were developed using either retrospective data [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] or prospective data previously collected for other purposes. [45][46][47][48][49] The start of data collection for the development cohorts spanned 36 years (1979-2015), and the duration of the cohort studies varying from 2 months up to 10 years for each cohort.…”
Section: Characteristics Of the Included Mortality Prediction Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics of the mortality prediction models and underlying derivation cohorts are presented in Table 1. In all, 19 mortality prediction models (44%) were developed using prospectively collected data specifically gathered for the development of the prediction model, 6,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] whereas 24 (56%) were developed using either retrospective data [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] or prospective data previously collected for other purposes. [45][46][47][48][49] The start of data collection for the development cohorts spanned 36 years (1979-2015), and the duration of the cohort studies varying from 2 months up to 10 years for each cohort.…”
Section: Characteristics Of the Included Mortality Prediction Modelsmentioning
confidence: 99%
“…Two mortality prediction models (4.7%) did not report the timespan during which their development cohort was assembled. 22,33 In all, 31 mortality prediction models (74%) were developed in a single country, 14,[18][19][20][21][22][23][24][25][26][27]29,31,[33][34][35][36][37][38][39][40][41][42][43][44][45]47,49 six (14%) in neighbouring countries (two or more) 6,13,28,30,32,46 and five (12%) were developed in multiple countries worldwide. [15][16][17]48 The number of patients included in the development databases ranged from 232 to 731 611 patients with a median of 4,895 (IQR 528-35 878).…”
Section: Characteristics Of the Included Mortality Prediction Modelsmentioning
confidence: 99%
“…The TMA score is a simple and rapidly measurable marker in clinical practice [15]. In our study, the speci c automated hematology analyzer can automatically measure TMA score during a CBC count and report the TMA score without additional costs, time, or laboratory tests [17,18]. During the early stage of TTM after OHCA, the TMA score can be valuable because it can indicate the changes in the morphological characteristics of schistocytes rather than the absolute schistocyte counts [39].…”
Section: Discussionmentioning
confidence: 98%
“…We previously found that increased TMA scores signi cantly predicted short-term mortality in patients with severe sepsis and septic shock [15,18]. To the best of our knowledge, no studies have reported that the new TMA score can predict the clinical outcomes of patients with OHCA.…”
Section: Introductionmentioning
confidence: 95%
“…Recent studies have found that peripheral blood IG not only plays an important role in the diagnosis of blood diseases, but also in the occurrence and development of inflammation and infectious diseases. Foreign scholars have found that under conditions where the body is accompanied by infection or systemic inflammation, then the number of peripheral blood circulating immature granu-locytes was significantly increased 11. However, the optimal threshold for evaluating bloodstream infection and contamination varies from one study to another (0.3%-0.55%) 12,13.…”
mentioning
confidence: 99%